2013
DOI: 10.3851/imp2721
|View full text |Cite
|
Sign up to set email alerts
|

Change in Vitamin D Levels and Risk of Severe Vitamin D Deficiency over 48 Weeks among HIV-1-Infected, Treatment-Naive Adults Receiving Rilpivirine or Efavirenz in a Phase III Trial (Echo)

Abstract: Rilpivirine had little effect on 25(OH)D, whereas efavirenz resulted in a significant reduction in 25(OH)D levels and an increase in the risk of severe 25(OH)D deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 35 publications
3
35
0
Order By: Relevance
“…Similar reductions in 25(OH)D levels were observed after 24 weeks of efavirenz or etravirine containing cART [29], whereas a clinical trial comparing efavirenz versus rilpivirine (both with 2NRTI) saw a significant 25(OH)D decrease (64.1-58.6 nmol/l) in the efavirenz group with unchanged levels (61.8-60.8 nmol/l) in the rilpivirine arm [30] (Table 2c). The results with nevirapine have been conflicting [31], with no changes in 25(OH)D observed in some studies [16,25,28], and reductions similar to those observed with efavirenz in others [22,24].…”
Section: Vitamin D Deficiency and Combination Antiretroviral Therapysupporting
confidence: 73%
See 1 more Smart Citation
“…Similar reductions in 25(OH)D levels were observed after 24 weeks of efavirenz or etravirine containing cART [29], whereas a clinical trial comparing efavirenz versus rilpivirine (both with 2NRTI) saw a significant 25(OH)D decrease (64.1-58.6 nmol/l) in the efavirenz group with unchanged levels (61.8-60.8 nmol/l) in the rilpivirine arm [30] (Table 2c). The results with nevirapine have been conflicting [31], with no changes in 25(OH)D observed in some studies [16,25,28], and reductions similar to those observed with efavirenz in others [22,24].…”
Section: Vitamin D Deficiency and Combination Antiretroviral Therapysupporting
confidence: 73%
“…The potential effect of cART on vitamin D status has received considerable attention recently; the emerging view is that specific antiretrovirals may affect 25(OH)D levels (Table 2) [4,[16][17][18][20][21][22][23][24][25][26][27][28][29][30]. Nonnucleoside-reverse transcriptase inhibitor (NNRTI)-based cART has most consistently been associated with low 25(OH)D levels [4,5,16,20,21], albeit not in all cross-sectional studies [6] ( Table 2a).…”
Section: Vitamin D Deficiency and Combination Antiretroviral Therapymentioning
confidence: 99%
“…In a randomized, double-blind, phase 3 trial, HIV patients who received efavirenz had significantly lower 25(OH)D levels at 48 weeks compared to those who received rilpivirine (-2.5 ng/mL; P < 0.0001 vs. no change) (Wohl et al 2014). In contrast, boosted protease inhibitor monotherapy appears to causes less risk for developing vitamin D insufficiency or deficiency (Cervero et al 2013).…”
mentioning
confidence: 96%
“…34 Brown and McComsey 35 evaluated 87 participants who were initiated on cART and found a 1.8 times higher risk of vitamin D deficiency in those started on efavirenz-based cART compared with non-efavirenzbased treatment regimen. More recently, Wohl and colleagues 36 showed that initiation of efavirenz resulted in a significant decrease in vitamin D levels, whereas initiation of rilpivirine had little effect on vitamin D. The MONET trial included 256 subjects who switched cART from either NNRTI-based or protease inhibitor (PI)-based therapy to boosted darunavir. At baseline, those on efavirenz had lower vitamin D levels.…”
Section: Factors Associated With Vitamin D Deficiency/insufficiencymentioning
confidence: 98%
“…The NNRTIs nevirapine and rilpivirine have not been found to be associated with vitamin D deficiency. 36,38 PIs inhibit 25-a-hydroxylase and 1-a-hydroxylase enzymes and consequently decrease production of the active form of vitamin D. 39 Lower bone mineral density (BMD) has been shown in several studies of subjects receiving PIs 22,40,41 ; however, a causal relationship with vitamin D deficiency has not been established.…”
Section: Factors Associated With Vitamin D Deficiency/insufficiencymentioning
confidence: 98%